2008
DOI: 10.1021/jf8024198
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Cost-Saving Approach To Optimize the Production of Subtilisin NAT by Submerged Cultivation of Bacillus subtilis Natto

Abstract: Subtilisin NAT, formerly designated nattokinase or subtilisin BSP, is a potent cardiovascular drug because of its strong fibrinolytic activity and safety. In this study, one Bacillus subtilis natto strain with high fibrinolytic activity was isolated. We further studied the optimal conditions for subtilisin NAT production by submerged cultivation and three variables/three levels of response surface methodology (RSM) using various inoculum densities, glucose concentrations, and defatted soybean concentrations as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
1
16
1
Order By: Relevance
“…Commercial NK production practices optimize the fermentation conditions to maximize the yield of NK produced by B. subtilis (natto), and include optimal temperature, pH, and fermentation time [26,27]. A variety of nutrients, such as glycerol, yeast extract, soy peptone, or shrimp shell powder have been examined for their ability to increase NK yield [28,29,30]. The optimal feed strategy used in in fed-batch fermentation methods has significantly enhanced NK production, relative to yields obtained by batch fermentation [31].…”
Section: Production and Purification Of Nattokinasementioning
confidence: 99%
“…Commercial NK production practices optimize the fermentation conditions to maximize the yield of NK produced by B. subtilis (natto), and include optimal temperature, pH, and fermentation time [26,27]. A variety of nutrients, such as glycerol, yeast extract, soy peptone, or shrimp shell powder have been examined for their ability to increase NK yield [28,29,30]. The optimal feed strategy used in in fed-batch fermentation methods has significantly enhanced NK production, relative to yields obtained by batch fermentation [31].…”
Section: Production and Purification Of Nattokinasementioning
confidence: 99%
“…The present findings on the interactive effect of production factors and influence of glucose on brevicin production corroborate results from Han et al (2011), indicating stimulation of Lactobacillus plantarum YJG bacteriocin production by optimized glucose concentration. Accordingly, Ku et al (2009) reported an increase in bacteriocin activity through Box-Behnken's design by optimizing the glucose concentration.…”
Section: Discussionmentioning
confidence: 99%
“…and marine creatures (Mahajan et al 2012;Sumi et al 1992;Wang et al 2009c). There are comprehensive studies regarding the optimal fermentation conditions for NK production (Berenjian et al 2014a;Chen and Chao 2006;Chen et al 2007a;Cho et al 2010;Deepak et al 2008;Ku et al 2009;Kwon et al 2011;Liu et al 2005;Rasagnya and Vangalapati 2013;Unrean et al 2012;Wang et al 2009b;Mahajan et al 2010). Concentration adjustment and feeding strategy of essential nutrients are critical for enhancing NK production.…”
Section: Nattokinase Production and Formulationmentioning
confidence: 99%
“…Moreover, we recently demonstrated that compared to the batch fermentation, the fed-batch addition of glycerol during the cell growth phase increases NK production significantly (Berenjian et al 2014a). Ku et al (2009) optimized the cultivation medium composed of defatted soybean and glucose. Defatted soybean is a by-product formed in salad oil manufacturing, and glucose is regarded a very common and cheap carbon source.…”
Section: Nattokinase Production and Formulationmentioning
confidence: 99%